2018
DOI: 10.1111/josi.12259
|View full text |Cite
|
Sign up to set email alerts
|

From Marginal to Mainstream and Vice Versa: Leaders’ Valuation of Diversity While in the Minority versus Majority

Abstract: This study examined tolerance and appreciation for differences within a group among leaders of numerically distinct factions (majority vs. minority), whose size remained stable or changed over time (majority ↔ minority). Appreciation or valuing differences in and of themselves was significantly higher among minority than majority leaders when their positions remained stable but not when their positions changed. Appreciation for differences decreased significantly when minority leaders became majority leaders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example, when speakers find that the attitudes of a group have shifted from initially opposed to being more congruent with their own views, the speakers’ confidence and comfort in the group increases ( Prislin et al, 2011 ). Other studies have examined shifts in group consensus and found a host of effects on variables such as group identification and openness to dissent ( Prislin et al, 2018 ). However, a small number of studies have examined how one person’s attitude change in a dyadic interaction affects aspects of the specific interaction and the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when speakers find that the attitudes of a group have shifted from initially opposed to being more congruent with their own views, the speakers’ confidence and comfort in the group increases ( Prislin et al, 2011 ). Other studies have examined shifts in group consensus and found a host of effects on variables such as group identification and openness to dissent ( Prislin et al, 2018 ). However, a small number of studies have examined how one person’s attitude change in a dyadic interaction affects aspects of the specific interaction and the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…These minorities, often primarily motivated to broaden their social acceptance, are likely to seek social change advocating for tolerance. Conversion and tolerance are fundamentally distinct paths to social change with different consequences for group dynamics ( Prislin et al, 2018 ). Change via conversion tends to weaken a group, at least immediately in its aftermath, as evident in former majority’s (majority → minority) dramatic decrease in group attachment and loyalty but former minority’s (minority → majority) only mild increase in attachment and loyalty to the group.…”
Section: Minorities Effect Social Change Over Time Winning a Competit...mentioning
confidence: 99%
“…The psychological processes underlying leaders’ responses to group diversity are thus paramount to the study of leadership and are undoubtedly impacted by the faction of the group from which the leader emerges. In the second article in this section, Prislin, Davenport, Xu, Moreno, and Honeycutt () present an experiment ( N = 141) studying changes in a group's majority or minority status. That is, a majority becoming a minority group, or a minority becoming a majority group.…”
Section: Three Challenges For Marginal Leadersmentioning
confidence: 99%